2017
DOI: 10.1002/eji.201747019
|View full text |Cite
|
Sign up to set email alerts
|

A new staining protocol for detection of murine antibody‐secreting plasma cell subsets by flow cytometry

Abstract: We provide a robust four-color fluorescence-based flow cytometry protocol that distinguishes viable dividing plasmablasts from nondividing plasma cells and, based on CD19 surface abundance, identifies two mature plasma cell populations in the spleen and the bone marrow of mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
133
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(143 citation statements)
references
References 19 publications
9
133
0
Order By: Relevance
“…B). Plasma cell differentiation negatively correlates with B220 expression . Notably, we observed that the ratio of B220 negative to B220 intermediate NP + CD138 + TACI + cells in BM were ∼2‐fold decreased in anti‐CD4 Ab‐treated mice (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…B). Plasma cell differentiation negatively correlates with B220 expression . Notably, we observed that the ratio of B220 negative to B220 intermediate NP + CD138 + TACI + cells in BM were ∼2‐fold decreased in anti‐CD4 Ab‐treated mice (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…2B) . B220 is expressed on the surface of B cells and downregulated during plasma cell differentiation (Pracht et al, 2017). We therefore defined three cell populations based on the levels of GFP fluorescence and B220 surface expression: GFP low B220 high , GFP int B220 int , GFP high B220 low , and a population negative for both markers (GFP neg B220 neg ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma cells were identified using the surface markers TACI and CD138 as described in Pracht et al. . For detection of intracellular APRIL and IL6, we fixed the cells for 30 min at room temperature with 3% PFA and permeabilized with 1% Triton X‐100 (Sigma) before adding Anti‐APRIL‐PE (A3D8, Biolegend) or Anti‐IL‐6‐PE (MP5‐20F3, Biolegend).…”
Section: Methodsmentioning
confidence: 99%